Assessment of the Logical Prescription of Albumin Drug According to Guideline and Patient Safety for Inpatients in Intensive Care Units of Iranian Hospital: A Cross-Sectional Study - Naghme Dashti; Hesamoddin Hosseinjani; Saeid Eslami; Seyed Mohammad Tabatabaei; Hasan Vakili Arki (Archives of Anesthesia and Critical Care)
Background: Medication errors in healthcare settings, including outpatient and hospital environments, pose a significant risk to patient safety. These errors can arise from incorrect dosages, drug interactions, contraindications, or inappropriate drug combinations. Methods: This study aimed to assess the logical prescription of albumin according to guidelines and patient safety for inpatients in the intensive care units of Imam Reza Hospital in Mashhad through a cross-sectional study. Methods: Data were collected over a 3-month period from albumin prescriptions in intensive care units, using a checklist based on information from prescription forms, patient files, and consultations. Results: The study found that 60.57% of albumin prescriptions were reviewed by DUE unit, with 51.53% complying with guidelines and 48.47% not. The highest prescription rate was in the Intensive Care Unit of Heart Surgery (ICUOH), at 36.83%, and the lowest in the Neonatal Intensive Care Unit (NICU), at 0.63%. The patient safety parameter, calculated based on correct/incorrect albumin prescriptions according to guidelines, showed an average safety of 67.10% across prescribing units and 62.34% based on indications. It reduced the financial burden caused by inappropriate prescriptions approximately $21,390 through DUE process. Conclusion: The research highlights the importance of continuous guideline-base DUE on rational drug utilization, patient safety and hospitals costs.